Aspek-Aspek Dimensi Waktu Tunggu Yang Mempengaruhi Kepuasan Pasien BPJS Rawat Jalan di Poliklinik Mata RSU William Booth Semarang - Insani, Rachel Ivonieta; Sriatmi, Ayun; Fatmasari, Eka Yunila (Jurnal Ilmiah Mahasiswa, 2020)
Background: One dimension of health care is characterized by patient waiting time. Waiting Time is a component that has the potential to cause satisfaction. Based on the results of preliminary studies that have been conducted at William Booth Hospital in Semarang related to patient waiting time and patient satisfaction is still not optimal.Methods: This research is a survey study using quantitative cross-sectional nature, on the participation of BPJS outpatients in the Eye Clinic. Sampling using a random sampling technique with a total sample of 95 people. Data analysis used univariate, bivariate and mutivariate analyzes.Results: The results showed the level of satisfaction of BPJS patients was 72.6%, cognitive aspects (p-value 0.001) with an OR value = 9.605, and affection aspects (p-value 0.002) with an OR value = 8.038.Conclusion: There is a significant difference between cognitive aspects and affection aspects with patient satisfaction. Cognitive aspects became the most dominant variable affecting patient satisfaction.